2018
DOI: 10.1111/obr.12762
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in polycystic ovary syndrome: a systematic review, meta‐analysis and meta‐regression

Abstract: Introduction: Women with polycystic ovary syndrome (PCOS) have increased risk of metabolic syndrome. The relative contribution of clinical, demographic or biochemical factors to metabolic syndrome in PCOS is not known. A literature search was conducted in MEDLINE, CINAHL, EMBASE and clinical trial registries. Of 4530 studies reviewed, 59 were included in the systematic review and 27 in the meta-analysis and meta-regression. In good and fair quality studies, women with PCOS had an overall increased prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 75 publications
3
136
1
7
Order By: Relevance
“…1 Weight difference of animals before and after treatment in the groups (mean ± SEM). ++ P < 0.01 PCO and 100 mg/kg of extract versus control, * P < 0.05, extract versus PCO (2) polycystic ovary [2,4]. Therefore, biochemical markers and ovarian biopsy are usual evidence for PCOS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Weight difference of animals before and after treatment in the groups (mean ± SEM). ++ P < 0.01 PCO and 100 mg/kg of extract versus control, * P < 0.05, extract versus PCO (2) polycystic ovary [2,4]. Therefore, biochemical markers and ovarian biopsy are usual evidence for PCOS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also raises the chances for some health problems, including diabetes mellitus, high blood pressure, cardiovascular disease, and endometrial cancer. This disorder has some physical signs in appearance such as hirsutism (excess facial and body hair), severe acne, and obesity [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed higher prevalence of MetS among women with PCOS in similar age groups, 17,18 ranging from 24% to 62% in women with overweight and obesity. [24][25][26] In two USbased studies, the prevalence of MetS in women with PCOS and BMI > 30 kg/m 2 was found to be 58.6%-61.8%.…”
Section: Discussionmentioning
confidence: 88%
“…A study from the United States showed that the prevalence of PCOS using the NIH-criteria was only minimally increased with obesity, 12 while a Spanish study showed that the prevalence of PCOS in women with overweight and obesity using the same criteria, was around 25%. 15,16 Women with PCOS, especially those with overweight or obesity, have a higher risk of developing MetS compared with a general population, 17 and this risk increases when using the NIH-diagnostic criteria compared to the Rotterdam consensus or androgen excess and PCOS Society criteria. 14 Metabolic syndrome (MetS) is a cluster of risk factors including obesity or abdominal obesity/increased waist circumference, dyslipidemia, hypertension and insulin resistance that increase the risk of developing type 2 diabetes and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation